Cost-effectiveness of mechanical thrombectomy using stent retriever after intravenous tissue plasminogen activator compared with intravenous tissue plasminogen activator alone in the treatment of acute ischaemic stroke due to large vessel occlusion in Spain. (September 2017) - de Andrés-Nogales, Fernando; Álvarez, María; de Miquel, María Ángeles; Segura, Tomás; Gil, Alberto; Cardona, Pere; Casado, Miguel Ángel; Nogueira, Raul G; Dávalos, Antoni
Introduction: To assess the cost-effectiveness of stent-retriever mechanical thrombectomy and intravenous tissue plasminogen activator compared with intravenous tissue plasminogen activator alone in patients with acute ischaemic stroke due to large vessel occlusions in Spain. Materials and methods: Clinical data were taken from the SWIFT PRIME clinical trial. A lifetime Markov state transition model defined by the modified Rankin Scale score was developed to estimate costs and health outcomes (life years gained and quality adjusted life years). A Spanish National Health System perspective (direct medical costs) was considered. Resource utilisation and utilities were obtained from available published data and endorsed by an expert panel. Costs (€, 2016) were obtained from various Spanish sources. Deterministic and probabilistic sensitivity analyses were performed. Results: Stent-retriever thrombectomy after intravenous tissue plasminogen activator was associated with better outcomes (1.17 life years gained and 2.51 quality adjusted life years) and savings of €44, 378, resulting in a dominant therapy over intravenous tissue plasminogen activator alone. A net monetary benefit of €119, 744 was obtained considering a willingness-to-pay threshold of €30, 000/quality adjusted life year gained. The combined therapy was also dominant in all sensitivity analyses, deterministic and probabilistic. Discussion: The results were consistent with a previously published cost-effectiveness analysis and reinforce the likeliness of the selection of stent-retriever mechanical thrombectomy plus intravenous tissue plasminogen activator over intravenous tissue plasminogen activator alone. Conclusion: Stent-retriever thrombectomy after intravenous tissue plasminogen activator is a dominant alternative over intravenous tissue plasminogen activator alone (more effective and less costly) for the treatment of acute ischaemic stroke patients with large vessel occlusions in the Spanish setting.